2015
DOI: 10.1051/fruits/2015038
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of commercially available products of aronia according to their metal content

Abstract: -Introduction.Among different fruit species, aronia have attracted a great attention because of its wide range of protective effects with potential benefits for human health. Furthermore, the consumption of products of aronia (juice, tea, berries) is becoming a part of a healthy lifestyle. Materials and Methods. The multi-element characterization of products of aronia has been carried out using inductively coupled plasma atomic emission spectrometry (ICP-AES). Results and Discussion. Among the major elements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 19 publications
1
26
3
1
Order By: Relevance
“…Among the micronutrients, the main micronutrient was Fe, followed by Zn, Mn, and Cu. Other authors [35] who analyzed the chemical composition of aronia leaves showed lower content of macronutrients but higher content of Fe and Zn than those reported by Cvetkowic et al [2]. The differences in the element concentrations in leaves were explained by the differences in the composition of soil and climatic conditions in which the plants were grown.…”
Section: Macro-and Microelementsmentioning
confidence: 73%
See 1 more Smart Citation
“…Among the micronutrients, the main micronutrient was Fe, followed by Zn, Mn, and Cu. Other authors [35] who analyzed the chemical composition of aronia leaves showed lower content of macronutrients but higher content of Fe and Zn than those reported by Cvetkowic et al [2]. The differences in the element concentrations in leaves were explained by the differences in the composition of soil and climatic conditions in which the plants were grown.…”
Section: Macro-and Microelementsmentioning
confidence: 73%
“…High intake of K, Mg, and Ca has been linked to reduced risk of stroke, hypertension, and osteoporosis [33]. Iron and other micro minerals are an essential part of many compounds in the oxygen transport and storage system and function as cofactors for enzymes [33][34][35]. Micronutrient Mo is a structural component of xanthine oxidase and xanthine dehydrogenase, which are crucial for urea synthesis [2].…”
Section: Macro-and Microelementsmentioning
confidence: 99%
“…Chokeberries also contain macroelements (K, Ca, P, Mg and Na), essential trace elements (Zn, Fe, Se, Cu, Mo, Cr), trace elements that are probably essential (Mn, Si, Ni, B, V) and toxic elements (Pb, Cd, Hg, As). Chokeberry fruit and products are potentially rich sources of K, Ca, P, Mg, Na, Fe and Zn [14,25,29]. Table 1 shows detailed data on the composition of chokeberry fruit and products.…”
Section: Botanical and Chemical Characteristicsmentioning
confidence: 99%
“…The consumption of anthocyanins, apart from their antioxidant activity, may be associated with an increase in endothelial nitric oxide and a reduction in the production of vasoconstrictor molecules, for example, angiotensin II, endothelins, and thromboxanes [115]. In addition to providing polyphenols, chokeberry is also a source of essential potassium [116]. In people with metabolic syndrome, a decrease in systolic (SBP) and diastolic (DBP) pressure have been reported after intervention with chokeberry extract [71,75,77].…”
Section: Impact Of Chokeberry On Blood Pressurementioning
confidence: 99%